Consumer ethnocentrism, cultural sensitivity, brand credibility on purchase intentions of domestic cosmetics - Ramadania Ramadania; Jaebeom Suh; Rosyadi Rosyadi; Bintoro Bagus Purmono; Rahmawati Rahmawati (Cogent Business & Management, 2023)
Brands investigate cultural sensitivity in order to stand out from global market competition and reach more diverse customers. The research emphasized on the relationship between consumer ethnocentrism, cultural sensitivity and brand credibility toward purchase intention to domestic products. The product category was cosmetic brands including Mustika Ratu, Sari Ayu, Wardah and Viva as the four top brands representing Indonesian cultural attitudes on the beauty of women. Meanwhile, cultural sensitivity determines the level of awareness, understanding, and acceptance of foreign-culture values. This study highlights consumer culture theory as the foundation for building a model of consumer ethnocentrism on the purchase intention of domestic products. This model focuses on the importance of cultural sensitivity as an antecedent that can influence consumer ethnocentrism and purchase intention of domestic products. The research was conducted using a survey method and also observed to be associative through the testing of the relationship between the variables contained in the conceptual model. The survey was conducted using WarpPLS 7.0. to 120 consumers of Indonesian cosmetics selected using the non-probability sampling method. The results concluded that cultural sensitivity has a negative influence on consumer ethnocentrism and purchase intentions of domestic brands. Brand credibility and consumer ethnocentrism were found to have a positive effect on domestic brand purchase intentions.
Keywords: D70; Z13; 650; brand credibility; Consumer ethnocentrism; cultural sensitivity; domestic brand; purchase intention